(Invited) CMOS Compatible High Performance IIIV Devices: Opportunities and Challenges. (4th May 2016) - Sun, Yanning; Shiu, Kuen-Ting; Cheng, Cheng-Wei; Majumdar, Amlan; Bruce, Robert; Yau, Jeng-bang; Farmer, Damon; Zhu, Yu; Hopstaken, Marinus; Frank, Martin M.; Ando, Takashi; Lee, Ko-tao; et al.
Abstract : Self-aligned InGaAs channel MOSFET has been demonstrated on both InP and Si substrate using CMOS compatible device structure and process flow. Peak transconductance GMSAT over 2200 μS/μm has been achieved, at L EFF = 30 nm and supply voltage V DD = 0.5 V. These processes and devices are well-suited for future generations of high-performance CMOS applications at short gate lengths and tight gate pitches.